PERAN ORANG TUA DALAM MEMBINA KARAKTER ANAK SHALEH SEBAGAI UPAYA MEWUJUDKAN MASYARAKAT MADANI MENUJU VISI RIAU 2020 - Nurhasanah Bakhtiar (Sosial Budaya, 2015)
This article discusses the role of parents in Riau in fostering children's character to realize the civil society towards the vision of Riau in 2020; and the factors that support and hinder the development of the character of the pious child. By taking locations in three districts in the province of Riau, namely Kampar, Bengkalis, and Pekanbaru, in the end the authors conclude that the role of parents in Riau in fostering children's character pious categorized as good; ie 81, 89%. The factors supporting general lack of awareness of parents, father and mother together about the importance of children's education pious. In addition, the availability of media such as television, radio, mobile phones, the Internet as a learning resource also support the successful development of a pious character of the child. While constraints are (1) low levels of parental education; (2) lack of religious understanding about educating children; (3) the low level of the economy; (4) lack of care and supervision of a parent due to busyness of parents with their duties, especially for mothers-career; and (5) the effect of the environment, peers, and electronic media.